Feasibility and Efficiency of Human Bone Marrow Stromal Cell Culture with Allogeneic Platelet Lysate-Supplementation for Cell Therapy against Stroke - Chengbo Tan; Hideo Shichinohe; Zifeng Wang; Shuji Hamauchi; Takeo Abumiya; Naoki Nakayama; Ken Kazumata; Tsuneo Ito; Kohsuke Kudo; Shigeru Takamoto; Kiyohiro Houkin (Stem Cells International)
Currently, there is increasing interest in human bone marrow stromal cells (hBMSCs) as regeneration therapy against cerebral stroke. The aim of the present study was to evaluate the feasibility and validity of hBMSC cultures with allogeneic platelet lysates (PLs). Platelet concentrates (PC) were harvested from healthy volunteers and made into single donor-derived PL (sPL). The PL mixtures (mPL) were made from three different sPL. Some growth factors and platelet cell surface antigens were detected by enzyme-linked immunosorbent assay (ELISA). The hBMSCs cultured with 10% PL were analyzed for their proliferative potential, surface markers, and karyotypes. The cells were incubated with superparamagnetic iron oxide (SPIO) agents and injected into a pig brain. MRI and histological analysis were performed. Consequently, nine lots of sPL and three mPL were prepared. ELISA analysis showed that PL contained adequate growth factors and a particle of platelet surface antigens. Cell proliferation capacity of PLs was equivalent to or higher than that of fetal calf serum (FCS). No contradiction in cell surface markers and no chromosomal aberrations were found. The MRI detected the distribution of SPIO-labeled hBMSCs in the pig brain. In summary, the hBMSCs cultured with allogeneic PL are suitable for cell therapy against stroke.